O nieprawidłowościach podczas auspicjów – wybrane przykłady - Elżbieta Loska (In Gremium. Studies in History, Culture and Politics, 2025)
As confirmed by all known versions of the legend of Romulus and Remus, from the very beginning of Rome,  almost every important manifestation of public activity was preceded by observations that were supposed to show the attitude of the gods, especially Jupiter, to human efforts.These observations were carried out independently by authorized members of the magistracy and by priests, namely augurs. Since auspicious signs had to be obtained to convene a people's assembly, pass a law, or elect officials, there was often a temptation to announce their appearance despite their real absence. Or the other way round: hide or ignore unfavorable signs.